Enhancing water and livelihood security and improving water productivity in tribal dominated paddy fallow agro-ecosystem of Odisha - D, Sethi; P, Nanda; S, Brahmanand P; A, Thakur; R, Mohanty; S, Mohanty; A, Mishra; M, Das; Chahal, V P (Indian Farming, 2022)
.